(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda the ancient traditional system of Indian medicine has two basic principles Tridosha And Panchbhuatic Chikitsa Siddhant. The elements of nature Earth, Water, Space, Fire and Air. All these elements are linked to the possibility of human life on Earth, and also contain compounds, minerals and nutrients that can improve our health. Krishna Mrittika is one of the most important elements of these and contains a lot of vital nutrients essential for the human body. The Acharyas told that Krishna Mrittika has Shothahar and Shoolhar Gunas. Krishna Mrittika can expel toxins from human body therefore is very useful in therapeutic and preventing many diseases. Ayurveda recommends Krishna Mrittika Chikitsa as a specialized therapy for good management of diseases. It is very Economic and effective also. It can be make easy methods. Its black colour absorbs all the colours of sun and According to the disease, affects the body organ. Solid and heavy human organs in the body are related to the Prithavi Mahaboot. As mentioned in Atharvaveda (12/1/6) that Prithavi detains lots of essential minerals, nutrients in it And by these minerals Prithavi nourishes the human Beings. This article, explaining how to use Krishna Mrittika as a therapeutic properties.